2000
DOI: 10.1097/00000658-200010000-00014
|View full text |Cite
|
Sign up to set email alerts
|

Complex Abdominal Wall Reconstruction: A Comparison of Flap and Mesh Closure

Abstract: ObjectiveTo analyze a series of patients treated for recurrent or chronic abdominal wall hernias and determine a treatment protocol for defect reconstruction. Summary Background DataComplex or recurrent abdominal wall defects may be the result of a failed prior attempt at closure, trauma, infection, radiation necrosis, or tumor resection. The use of prosthetic mesh as a fascial substitute or reinforcement has been widely reported. In wounds with unstable soft tissue coverage, however, the use of prosthetic mes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
208
0
6

Year Published

2007
2007
2015
2015

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 283 publications
(215 citation statements)
references
References 23 publications
1
208
0
6
Order By: Relevance
“…Furthermore, at follow-ups, no hernia relapses occurred. Mathes et al (2000) reported on 100 cases in which the tensor fasciae latae was used to reconstruct abdominal wall damage after infected mesh removal. In these cases, using the component separation technique had its own limitations: the tensor fasciae latae was difficult to dissociate for umbilical defect repair; and after the flap was overturned, the dissociated vessel pedicle at the inguinal area exerted pressure on the femoral vein, increasing the risk of deep vein thrombosis.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, at follow-ups, no hernia relapses occurred. Mathes et al (2000) reported on 100 cases in which the tensor fasciae latae was used to reconstruct abdominal wall damage after infected mesh removal. In these cases, using the component separation technique had its own limitations: the tensor fasciae latae was difficult to dissociate for umbilical defect repair; and after the flap was overturned, the dissociated vessel pedicle at the inguinal area exerted pressure on the femoral vein, increasing the risk of deep vein thrombosis.…”
Section: Discussionmentioning
confidence: 99%
“…Anterior abdominal wall defects are classified into two groups based on defect components [1]: Type I with intact or stable skin coverage over hernia defect and Type II with unstable or absent skin coverage over hernia defect. The defects are assigned Zones based on primary defect location to assist in the selection and evaluation of their treatment: Zone 1A, upper midline; Zone IB, lower midline; Zone 2, upper quadrant; Zone 3, lower quadrant.…”
Section: Discussionmentioning
confidence: 99%
“…The disadvantages of Gore-Tex mesh are poor fixation to musculofascial layer due to poor tissue ingrowth resulting in higher incidence of reherniation and high cost of this material. The use of synthetic mesh requires adequate soft tissue coverage to avoid complications [7]. We have resorted to use of island omental flap or expanded skin whenever native skin and soft tissues are inadequate to cover the alloplastic material.…”
Section: Discussionmentioning
confidence: 99%